2011
DOI: 10.1590/s0104-07072011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Rede social de apoio no Brasil: grupos e linhas de pesquisa

Abstract: RESUMO: Trata-se de uma pesquisa descritiva documental cujo objetivo foi descrever o perfil dos grupos de pesquisa, cadastrados no Conselho Nacional de Desenvolvimento Científico e Tecnológico que trabalham a temática rede social de apoio. A busca dos dados deu-se a partir do Diretório dos Grupos de Pesquisa no Brasil, no segundo semestre de 2009. Foram identificados 20 grupos, 22 linhas de pesquisa e 139 pesquisadores. Os resultados demonstraram um perfil diversificado dos grupos em relação às áreas de conhec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…On this, the authors point out that the support of family and friends can motivate the practice of physical exercises, as demonstrated in a study with people with hypertension developed in Paraná. This study, when evaluating the social support, identified that the family is the main source of support, including material, emotional and cognitive assistance (20) . Other RF that contributed to the prevalence of SL were: "lack of training for accomplishment of physical exercise" (37%) and "activity intolerance" (26%).…”
Section: Discussionmentioning
confidence: 99%
“…On this, the authors point out that the support of family and friends can motivate the practice of physical exercises, as demonstrated in a study with people with hypertension developed in Paraná. This study, when evaluating the social support, identified that the family is the main source of support, including material, emotional and cognitive assistance (20) . Other RF that contributed to the prevalence of SL were: "lack of training for accomplishment of physical exercise" (37%) and "activity intolerance" (26%).…”
Section: Discussionmentioning
confidence: 99%